Cystic duct carcinoma mimicking a middle bile duct tumour. (27th March 2015) - Francisco, Elsa; Mendes, Miguel; Vale, Sílvio; Esteves, Joana
Abstract : Cystic duct carcinoma was defined by Farrar as a tumour restricted to the cystic duct, making it a rare disease. The authors describe a case of a cystic duct carcinoma that fulfils Farrar's strict diagnostic criteria and that became clinically relevant by compressing the common hepatic duct, thus causing cholestasis. A cholecystectomy was performed with en bloc resection of the cystic and extrahepatic bile duct with a regional lymphadenectomy.